2021
DOI: 10.3389/fcell.2021.648856
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Cachexia-Inducing Factors in Diffuse Large B-Cell Lymphoma Reveals a Molecular Subtype and a Prognosis-Related Signature

Abstract: BackgroundCachexia is defined as an involuntary decrease in body weight, which can increase the risk of death in cancer patients and reduce the quality of life. Cachexia-inducing factors (CIFs) have been reported in colorectal cancer and pancreatic adenocarcinoma, but their value in diffuse large B-cell lymphoma (DLBCL) requires further genetic research.MethodsWe used gene expression data from Gene Expression Omnibus to evaluate the expression landscape of 25 known CIFs in DLBCL patients and compared them with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…We applied integrated bioinformatics methods, including MCPcounter, xCell, quanTIseq, CIBERSORTx, single-sample gene set enrichment analysis (GSEA) to evaluate differences of immune status among different molecular subtypes ( Finotello et al, 2019 ; Cai et al, 2021 ; Yuan et al, 2021 ). Furthermore, the ‘‘pRRophetic’’ R package was used to predict the chemotherapy response of each sample based on Genomics of Drug Sensitivity in Cancer (GDSC) 3 , and the correlation between molecular subtypes and immune checkpoint genes was analyzed ( Geeleher et al, 2014 ; Kuang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…We applied integrated bioinformatics methods, including MCPcounter, xCell, quanTIseq, CIBERSORTx, single-sample gene set enrichment analysis (GSEA) to evaluate differences of immune status among different molecular subtypes ( Finotello et al, 2019 ; Cai et al, 2021 ; Yuan et al, 2021 ). Furthermore, the ‘‘pRRophetic’’ R package was used to predict the chemotherapy response of each sample based on Genomics of Drug Sensitivity in Cancer (GDSC) 3 , and the correlation between molecular subtypes and immune checkpoint genes was analyzed ( Geeleher et al, 2014 ; Kuang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we embarked on a comprehensive analysis of histology-specific lactate-related gene expression data from DLBCL samples, and develop a novel prognostic gene signature. Compare with other four published models (13)(14)(15)(16), the clinical usefulness of our novel prognostic model was better. Our findings revealed a significant correlation between the prognostic lactate score and various key factors including patient outcomes, immune infiltration levels, and activation of cancer-related pathways in DLBCL.…”
Section: Discussionmentioning
confidence: 74%
“…The data generated in the present study further suggest that PLA2G7 expression may be associated with DLBCL tumor stromal and immune scores. Kua et al [ 31 , 32 ] reported that the CIBERSORT algorithm was used to analyze the DLBCL immune cell infiltration in the TME. As such, we explored the association between PLA2G7 expression and TIICs, revealing that patients expressing high levels of this gene also exhibited increased monocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%